2022
DOI: 10.1093/hropen/hoac053
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord platelet-rich plasma to treat endometrial pathologies: methodology, composition and pre-clinical models

Abstract: STUDY QUESTION Can human umbilical cord platelet-rich plasma (hUC-PRP) efficiently treat endometrial damage and restore fertility in a preclinical murine model? SUMMARY ANSWER Local application of hUC-PRP promotes tissue regeneration and fertility restoration in a murine model of Asherman syndrome and endometrial atrophy (AS/EA). WHAT IS KNOWN ALREADY AS/EA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Recent study have found that CBP contains low concentrations of proinflammatory cytokines (IL‐2, IL‐6, IFN‐γ, and TNF‐α), elevated chemokine IL‐8 and higher levels of VEGF, G‐CSF, EGF, and FGF‐basic growth factors, which promote mononuclear cell viability and reduced apoptotic cell death in vitro and improve neurodegenerative diseases (Ehrhart et al, 2018). Further, several studies have explored the effects of cytokines on ovarian function (Rodríguez‐Eguren et al, 2023; Said et al, 2016). Recent studies have shown that the messenger RNA (mRNA) levels of IL‐6 and IL‐8 in ovarian tissue are significantly upregulated, while concomitant reduction in ovarian anti‐inflammatory cytokine IL‐10 mRNA level (Said et al, 2016; Walsh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study have found that CBP contains low concentrations of proinflammatory cytokines (IL‐2, IL‐6, IFN‐γ, and TNF‐α), elevated chemokine IL‐8 and higher levels of VEGF, G‐CSF, EGF, and FGF‐basic growth factors, which promote mononuclear cell viability and reduced apoptotic cell death in vitro and improve neurodegenerative diseases (Ehrhart et al, 2018). Further, several studies have explored the effects of cytokines on ovarian function (Rodríguez‐Eguren et al, 2023; Said et al, 2016). Recent studies have shown that the messenger RNA (mRNA) levels of IL‐6 and IL‐8 in ovarian tissue are significantly upregulated, while concomitant reduction in ovarian anti‐inflammatory cytokine IL‐10 mRNA level (Said et al, 2016; Walsh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The immune regulatory network can play an essential role in the restoration for POI, which achieves the treatment by modulating the inflammatory microenvironment (Huang et al, 2021). Previous studies have shown that cytokines and growth factors in PRP derived from hUCB can effectively improve ovarian function and hormone levels in POI (Cakiroglu et al, 2020; Panda et al, 2020; Rodríguez‐Eguren et al, 2023; Sfakianoudis et al, 2020). It is clear from previous research that CBP was shown to be richer for cytokines and growth factors compared to ABP and PRP (Ehrhart et al, 2018; Rhéaume et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot investigation, C57BL/6 mice bearing the Asherman syndrome and endometrial atrophy were utilized to evaluate the effectiveness of human umbilical cord PRP in tissue regeneration and reproductive restoration. In the murine model, it was found that human Umbilical Cord PRP (hUC-PRP) increased reproductive rates when infused into the uterine cavity on the thirteenth day of the HRT cycle [171].…”
Section: Gynecologymentioning
confidence: 99%
“…Their proteomic analyses revealed overexpression of HOXA10, related to endometrial functionality, and proteins involved in angiogenesis, mitotic cell cycle, PI3K/AKT and JAK/STAT signaling pathways. Rodríguez-Eguren et al [231] characterized thoroughly the composition of hUC-PRP processed after manual and commercial strategies. Then, its regenerative effect alone or driven by the aforementioned EndoECM was evaluated in a mouse model of AS/EA.…”
Section: Plasma and Platelet-rich Plasmamentioning
confidence: 99%